Synthesis and characterization of heterobimetallic SnIV–CuII/ZnII complexes: DFT studies, cleavage potential and cytotoxic activity. Issue 4 (3rd March 2020) - Afzal, Mohd; Usman, Mohammad; Al-Lohedan, Hamad A.; Tabassum, Sartaj
Abstract: Heterobimetallic complexes [Cu(L)Sn(CH3 )2 (H2 O)(Cl)] (3 ) and [Zn(L)Sn(CH3 )2 (H2 O)(Cl)] (4 ) have been synthesized from their monometallic analogs [Cu(L)(H2 O)(Cl)] (1) and [Zn(L)(H2 O)(Cl)] (2 ) of Schiff base ligand (L ) which were characterized by various spectroscopic and analytical methods. DFT calculations were carried out to simulate the vibrational spectra to support the anticipated structures. The interaction studies of ligand (L ) and complexes (1 –4 ) with CT–DNA were performed by employing UV–vis, and fluorescence spectroscopic techniques which revealed that heterobimetallic complexes 3 and 4 showed higher affinity with DNA due to dual mode of action as compared to monometallic complexes 1 and 2 . Further, validation of the interaction studies was accomplished by carrying out molecular docking studies with DNA. Gel assay displayed that both the complexes have ability to cleave DNA efficiently and are specific minor groove binders. Cu II –Sn IV complex 3 cleaved pBR322 DNA via oxidative mechanism, while Zn II –Sn IV complex 4 followed hydrolytic cleavage pathway. In vitro cytotoxicity evaluation of complex 3 was tested on a different cancer cell lines showing promising antitumor activity. Communicated by Ramaswamy H. Sarma